Design and Simulation of MEMS Moisture Sensor Using COMSOL Multiphysics Software - Nazrin Ismail, Muhamad; Yusoff, Noriah; Hayati Saad, Nor; Abd Rashid, Amirul (International Journal of Engineering and Technology, 2018)
Micro-electro-mechanical system (MEMS) is a hybrid technology that combines electronic, electric and mechanical technology in a micron-size system. This allowed for higher performance and multifunction devices fabricated at much lighter weight and cost effective. One of the major application of MEMS is in sensor devices area. This paper highlight the simulation study of a typical moisture sensor fabricated from Tungsten Interdigitated (IDE) MEMS device. Using COMSOL Multiphysics software, the moisture sensor was modelled based on the current material and physical dimension and layout. The model then go through validation proses to its sensitivity performance against the experimental result. Subsequently, the optimization on sensor sensitivity was carried out by varying the model parameters including the sensor physical dimension, working temperature and humidity. The simulation result suggest that the sensor sensitivity is highly correlated to the electrode distance value. The average sensitivity of the sensor improved to ~48% better when the distance between reduced to 50% from 6 micron to 3 micron tested at temperature between 25 ÌŠ C to 45 ÌŠ C. This information is valuable as the input to the sensor designer in finalizing the MEMS physical layout in producing highly sensitive moisture sensor devices.Â Â